TERMINAL DAN STASIUN KERETA API SEBAGAI PRASARANA MODA TERINTEGRASI TRANSPORTASI KOMUTER REGIONAL DAN LOKAL BERKONSEP WAYFINDING DI KOTA DEPOK - Astika Aprilliana; MD Edi Purnomo; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2016)
Bus terminal and railway station’s planning and designing in Depok motivated by the government's plan in realizing an integrated transportation in this city. The need of bus terminal and train station’s integration is to easily facilitate the movement and displacement modes for the user of transportation mode (commuter) especially in Depok City. Design issues found is that how can the circulatory sistem be able to facilitate the movement and displacement modes for commuters, that are efficient, swift, and safe, also accommodated its building system. The design method used the concept of wayfinding. The application of wayfinding concept is able to resolve the design issues such as the design of circulatory sistem, which are efficient, swift, and safe, also accommodated its building system. In the wayfinding concept, users are the main concern, specifically on the movement and displacement towards a mode. According to the wayfinding concept, the problem solving is that the users make and execute the decision, also know and understand their environment. It influences the design of wayfinding with circulation planning and space layout, also the information design, in order to reach the success of wayfinding design which are efficient, swift, and safe, and accommodated its building system.